REKAYASA ULANG DAN PEMBUATAN PROTOTIPE SLURRY ICE MACHINE BERKAPASITAS 0,7 TON DENGAN METODE SCRAPED-SURFACE - Nur Mahmudi Ismail; Eko Fajar Nurprasetyo; Nurjanah Nurjanah; Hafit Isandono; Mohamad Taufik; Mala Nurilmala; Tati Nurhayati; Ahmad Syihan Ismail; Mahyudi Mahyudi (Fakultas Perikanan dan Ilmu Kelautan, 2021)
Reengineering and prototype production of slurry ice machine using Scraped-surface methode of evaporator wich is called Ice Porridge Making Machine has been conducted to be operated in tropical area especially, Indonesia. Reengineering and slurry ice production was conducted toward the sampel acquired from commercial market. The reengineered machine could produce slurry ice with ice cristal fraction of 30-40% and liquid fraction of 60-70%. Furthermore, a 1 ton/24 hours prototype of slurry ice machine was designed and produced. The machine successfully produced slurry ice of 700 kg/24 hours capacity, then it was tested for durability transporting by a pick-up from Depok, West Java to Lampung, Tasikmalaya, West Java, operated using brackish water at shrimp farm; and Tanjung Lesung, Banten operated with sea water on 35 GT fishing vessel. The machine could produce slurry ice using sea water, brackish water, and solution of 4.0% NaCl. The slurry ice produced was effectively used to preserve the freshness of shrimps from South Lampung and Tasikmalaya compared of using crushed ice. Shrimp preserved by crushed ice showed blackened color at the fifth day storage, while shrimp preserved by slurry ice still looked fresh on 14th day of storage. All Indonesian fishermen and fishery industry should recognize and motivated applying slurry ice technology to improve their quality and productivity.